2023
DOI: 10.1051/0004-6361/202245812
|View full text |Cite
|
Sign up to set email alerts
|

Traveling kink oscillations of coronal loops launched by a solar flare

Abstract: Context. Kink oscillations, which are often associated with magnetohydrodynamic waves, are usually identified as transverse displacement oscillations of loop-like structures. However, the traveling kink oscillation evolving to a standing wave has rarely been reported. Aims. We investigate the traveling kink oscillation triggered by a solar flare on 2022 September 29. The traveling kink wave is then evolved to a standing kink oscillation of the coronal loop. Methods. The observational data mainly come from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…This setup could capture the propagation of a single transverse swaying motion passing through different heights from bottom to top along the vertical threads. It is found that there was a time delay of the peaks among these wave structures marked by the yellow and blue plus signs in Figures 4 and 5, suggesting that these swaying motions correspond to traveling waves, a phenomenon also observed in coronal loops (e.g., Li et al 2023). According to the peaks of these wave structures, we plot the height of the peaks for each swaying motion, represented by the height of each cut with respect to time, as shown in the white box in panels (a6) in Figures 4 and 5.…”
Section: Characteristics Of the Swaying Motionsmentioning
confidence: 74%
“…This setup could capture the propagation of a single transverse swaying motion passing through different heights from bottom to top along the vertical threads. It is found that there was a time delay of the peaks among these wave structures marked by the yellow and blue plus signs in Figures 4 and 5, suggesting that these swaying motions correspond to traveling waves, a phenomenon also observed in coronal loops (e.g., Li et al 2023). According to the peaks of these wave structures, we plot the height of the peaks for each swaying motion, represented by the height of each cut with respect to time, as shown in the white box in panels (a6) in Figures 4 and 5.…”
Section: Characteristics Of the Swaying Motionsmentioning
confidence: 74%
“…Later also low-amplitude propagating waves were detected with the Coronal Mulyi-Channel Polarimeters (CoMP). They have been observed propagating along coronal loops and plumes (Tomczyk et al, 2008;Morton, Weberg, and McLaughlin, 2019;Yang et al, 2020;Morton et al, 2021;Li et al, 2023). Propagating kink oscillations have been also observed in solar prominences (Okamoto et al, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…This may be a reasonable view of oscillations excited impulsively in the corona (e.g. from a nearby solar flare; Nakariakov et al 1999 ;Li et al 2023a ). In this paradigm, the large density gradients in the transition region may act as ef fecti ve reflectors of wave energy, ef fecti vely forming wave nodes in the upper transition region.…”
Section: Seismological Implicationsmentioning
confidence: 99%